2019
DOI: 10.12968/jowc.2019.28.sup9.s28
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence imaging guided dressing change frequency during negative pressure wound therapy: a case series

Abstract: Objective: Knowledge of wound bioburden can guide selection of therapies, for example, the use of negative pressure wound therapy (NPWT) devices with instillation in a heavily contaminated wound. Wound and periwound bacteria can be visualised in real-time using a novel, non-contact, handheld fluorescence imaging device that emits a safe violet light. This device was used to monitor bacterial burden in patients undergoing NPWT. Methods: Diverse wounds undergoing NPWT were imaged for bacterial (red or cyan) fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…This is not the first study to report bacterial fluorescence from the periwound region. In a clinical trial of 50 hard-to-heal (chronic) wounds, Raizman et al reported fluorescence indicative of bacteria in the periwound of 89% of wounds 20 and Farhan et al detected bacteria in the peripheries of 88% of wounds. 25 However, we show here for the first time that the presence of periwound bacterial loads is associated with delayed healing and fluorescenceguided debridement of these regions to eliminate fluorescent signature from bacteria was associated with a shift of wounds onto a healing trajectory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not the first study to report bacterial fluorescence from the periwound region. In a clinical trial of 50 hard-to-heal (chronic) wounds, Raizman et al reported fluorescence indicative of bacteria in the periwound of 89% of wounds 20 and Farhan et al detected bacteria in the peripheries of 88% of wounds. 25 However, we show here for the first time that the presence of periwound bacterial loads is associated with delayed healing and fluorescenceguided debridement of these regions to eliminate fluorescent signature from bacteria was associated with a shift of wounds onto a healing trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…18 Wounds exhibiting red or cyan fluorescence are considered to have moderate to heavy (>10 4 CFU/g) levels of bacteria. 13,[20][21][22] The wound care clinician captured standard and fluorescence images after training on device use and image interpretation. 18,23 A range finder on the device was used to ensure that all images were taken at the optimal imaging distance (8-12cm).…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this challenge, a disposable drape attachment can be used, and work has demonstrated its effectiveness in achieving the required darkness. 16…”
Section: Limitationsmentioning
confidence: 99%
“…The MolecuLight i:X imaging device is a novel, handheld, point-of-care diagnostic imaging tool designed to accurately and digitally measure wound areas and to provide objective, real-time evidence on the presence and location of high bacterial loads (both planktonic and in biofilm. [11][12][13][14][15][16] This provides objective documentation, performed at the bedside, during which the device captures an image in a format compatible with most electronic medical records (EMR) systems. The device contains built-in digital wound measurement software and emits a safe violet light which is used for non-invasive, contrast agent free fluorescence imaging to identify regions with concerning levels of bacteria in real-time.…”
mentioning
confidence: 99%